2021
DOI: 10.3390/healthcare9121608
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Mortality in Critically Ill Patients with SARS-CoV-2 Infection: A Multicenter Study in the Kingdom of Saudi Arabia

Abstract: Background: SARS-CoV-2 infection has a high mortality rate and continues to be a global threat, which warrants the identification of all mortality risk factors in critically ill patients. Methods: This is a retrospective multicenter cohort study conducted in five hospitals in the Kingdom of Saudi Arabia (KSA). We enrolled patients with confirmed SARS-COV-2 infection admitted to any of the intensive care units from the five hospitals between March 2020 and July 2020, corresponding to the peak of recorded COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…Regarding ICU mortality, our results are consistent with a multicenter study in Saudi Arabia in which 229 patients with COVID-19 pneumonia were treated in the ICU; the mortality rate was 37%. 21 Our results were lower than those of other studies. In a meta-analysis of 24 studies published in PubMed, MEDLINE, Cochrane, and EMBASE databases by May 31, 2020 (10,150 patients), the combined ICU mortality rate was 41.6%.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Regarding ICU mortality, our results are consistent with a multicenter study in Saudi Arabia in which 229 patients with COVID-19 pneumonia were treated in the ICU; the mortality rate was 37%. 21 Our results were lower than those of other studies. In a meta-analysis of 24 studies published in PubMed, MEDLINE, Cochrane, and EMBASE databases by May 31, 2020 (10,150 patients), the combined ICU mortality rate was 41.6%.…”
Section: Discussioncontrasting
confidence: 88%
“…This is consistent with many studies that reported that critically ill patients with COVID-19 pneumonia have significantly higher D-dimer levels, which can be used as a prognostic marker for in-hospital mortality. 2 , 21 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, both serum iron and transferrin are found to be inversely correlated with proinflammatory cytokines such as interleukin-6; thus, low serum iron and transferrin levels are associated with a poor prognosis in SARS-CoV-2 infection cases [ 15 ]. Moreover, elevated serum ferritin levels have also been linked to an increased risk of severe COVID-19 [ 16 ], ICU admission, and mortality rate [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 showed the flow chart of related literature search and selection process. A total of twenty-three articles with 573,928 COVID-19 patients were eligibly included in this quantitative meta-analysis [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ]. The characteristics of the eligible studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%